The Irony in the Collection (Mat Albanafsaj) Stories by Abdullah Ab (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Abdullah Abd one of the writers of (black humor), in which laughter does not come from comedy, but from the intense emotion generated by the contradiction based on irony.The synthesis of contradictions is the essence of the irony and its truth in his storytelling, which suggests a sense of irony and ugliness. That synthesis is not subject to the rules of the possible and the reasonable, or the conceptions of the mind; Things have their own laws and their own logic. And in the irony lies the key to his vision of the world and his irony starts from the first titles and narrative thresholds then runs through the stories and escalates at the end to a sharp tense emotion.His irony varies between: a verbal irony, an events irony, a situation irony, a romantic irony, and a kinetic irony. In all cases, it characterized by richness, and expresses the contradiction in a concise language that opens up about the individual’s tragedy, and his lost experiences in front of others; The narrator presents an inconsistent and unbalanced world based on a broken vision explained by the contradiction in the signs and the difference between the meanings.